Not so individual after all: An ecological approach to age as an individual difference variable in a classroom - Pfenninger, Simone E. (Studies in Second Language Learning and Teaching, 2017)
The main goal of this paper is to analyze how the age factor behaves as an alleged individual difference (ID) variable in SLA by focusing on the influence that the learning context exerts on the dynamics of age of onset (AO). The results of several long-term classroom studies on age effects will be presented, in which I have empirically analyzed whether AO works similarly across settings and learners or whether it is influenced by characteristics of the setting and the learner—and if so, whether there are contextual variables that can help us understand why those outcomes are different. Results of multilevel analyses indicate that macro-contextual factors (i.e., the wider school context) turn out to have a mediating effect on the relation between AO and L2 proficiency increase, exerting both positive and negative influences and thus suggesting that AO effects are malleable, which is what one would expect if we are dealing with an ID variable. In contrast, no such phenomenon can be observed in relation to lower contextual levels; learners within classes do not vary with regard to how sensitive they are to AO. Since the broader social environment in which learning takes place seems to be more influential than the cognitive state assumed to be a characteristic of the individual, I suggest that an ID model that assumes that age is a “fixed factor” (Ellis, 1994, p. 35) is not entirely satisfactory.